2017
DOI: 10.1093/ndt/gfx209
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between iron dose, hospitalizations and mortality in incident haemodialysis patients: a propensity-score matched approach

Abstract: Intravenous iron administration is advisable for maintaining haemoglobin levels in patients that receive haemodialysis. Our data suggested that large monthly iron doses, adjusted for body weight, were associated with more hospitalizations, but not with mortality or infection-related hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…If sufficient iron is not available for erythropoiesis, this can lead to inappropriate escalation of erythropoiesis-stimulating agent (ESA) therapy, which is associated with adverse outcomes in both adults and children [58]. Conversely, iron overload also has negative sequelae including free radical tissue damage, increased risk of systemic infection, and more hospitalizations [911]. Achieving the optimal balance of bioavailable iron for erythropoiesis in children with advanced CKD is therefore paramount in anemia management; however, it remains challenging for pediatric nephrologists.…”
Section: Introductionmentioning
confidence: 99%
“…If sufficient iron is not available for erythropoiesis, this can lead to inappropriate escalation of erythropoiesis-stimulating agent (ESA) therapy, which is associated with adverse outcomes in both adults and children [58]. Conversely, iron overload also has negative sequelae including free radical tissue damage, increased risk of systemic infection, and more hospitalizations [911]. Achieving the optimal balance of bioavailable iron for erythropoiesis in children with advanced CKD is therefore paramount in anemia management; however, it remains challenging for pediatric nephrologists.…”
Section: Introductionmentioning
confidence: 99%
“…The same group [30] observed no consistent association between IV iron dose and risk for all-cause, cardiovascular, or infectious hospitalizations, even among patients receiving iron doses exceeding 2100 mg over a period of 6 months. A new multicenter observational study of the safety of IV iron supplementation in incident HD patients showed that larger iron doses infused over time were not associated with mortality, after adjusting for potential confounding factors [31]. Furthermore, a recent systematic review and meta-analysis of 7 randomized controlled trials and 15 observational studies including more than 140,000 patients treated with HD, found no evidence of increased risk of infection, cardiovascular events, hospitalizations, or mortality with the use of higher-dose IV iron compared with lower doses [32].…”
Section: Discussionmentioning
confidence: 99%